Alcohol consumption and allergic diseases: Mendelian randomization evidence from China - Chen Zhu; Timothy Beatty; Yingxiang Li; Gang Chen; Qiran Zhao; Qihui Chen (Global Health Action)
Background The prevalence of allergic diseases in China has risen significantly over the past decades, affecting the quality of life for approximately 40% of the population. Objectives This study aimed to integrate survey and genomic data to explore the potential causal relationship between alcohol consumption and allergic diseases. Method In collaboration with a leading genetic testing company in China, we collected data on 3,041 participants via an online survey between December 2018 and October 2019. A Mendelian Randomization (MR) design was employed in data analysis, leveraging the random allocation of genes at meiosis in humans to create instrumental variables for alcohol intake. This method was used to estimate the causal effect of alcohol consumption on the incidence of allergic diseases. Results While ordinary least-squares estimates showed a negative association between alcohol drinking and the risk of self-reported allergic diseases, MR estimates suggest that higher alcohol consumption increased the risks of allergy in certain subgroups. Specifically, predicted drinking [b = 0.445, p = 0.032] and the number of drinking times during the past 30 days [b = 0.031, p < 0.01] were associated with higher risks of allergic diseases among females. We found little evidence of a causal impact of alcohol intake on allergic diseases in men. Conclusion Higher alcohol intake is causally associated with a higher risk of allergic diseases in Chinese women but not men.